Gambaran Eritrosit Ayam Broiler Dengan Waktu Tempuh Transportasi dan Level Pemberian ZnSO4 Berbeda - Parwati, E. D.; Ulupi, N.; Afnan, R.; Satyaningtijas, A. S. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
Transportation of broiler chickens in Indonesia from cage to traditional slaughterhouse has the potential to cause stress because it does not heed the elements of animal welfare. Thus, this study aims to examine the impact of transport time to hematological value with ZnSO4 given in broiler chickens. The research design used was Randomized Block Design (RAK) of factorial with two treatment factors. Treatment factors are transport time (1, 2, and 3 hours) and supplementation of ZnSO4 (0, 80, and 160 ppm). Total of 144 male broiler chickens aged 4 weeks were the object of observation. Transportation performed in the early morning. Parameters studied were hematology value which are consists of erythrocyte count, hemoglobin level, hematocrit value, and erythrocyte index. The data analysis was done statistically using IBM SPSS version 20. Transport time proved to affect hematological value of birds seen from the changes, which are decrease of erythrocyte count and hematocrit values. Birds were indicated microcytic anemia based on low MCV value. Supplementation of ZnSO4through drinking water at 80 and 160 ppm for 7 days prior to slaughter was able to maintain hemoglobin and MCH as well as MCHC of birds up to 2 hours of transport time.